PENGARUH TERAPI RELAKSASI AUTOGENIK BERBASIS ISLAMI TERHADAP TINGKAT KECEMASAN PASIEN CVA : THE EFFECT OF ISLAMIC-BASED AUTOGENIC RELAXATION THERAPY ON ANXIETY LEVELS IN CVA PATIENTS - Ninik Eva Maulidia; Faridah, Virgianti Nur; Lestari, Trijati Puspita (Jurnal Keperawatan Muhammadiyah, 2025)
Background :Psychological disorders are common in CVA patients. Anxiety is one of the psychological factors that can worsen the condition of CVA patients. Islamic-based autogenic relaxation therapy is an alternative for reducing anxiety. Objective :This study aims to understand the impact of islam-based autogenic relaxation therapy on anxiety levels in patients with CVA in the Bougenville Ward of Dr. Soegiri Regional Hospital, Lamongan Regency. Methods : This study used a pre-experimental design with a single-group pre-test and post-test approach. Using consecutive sampling, 36 CVA patients were recruited. The study used the HADS-A instrument to measure anxiety levels and the HMS instrument to measure mobility levels. Islamic-based autogenic relaxation therapy was administered for three consecutive days according to standard operating procedures (SOP). The data were analyzed using the Wilcoxon test with a P-value of 0.05. Result : Before the intervention, 80.6% of CVA patients experienced moderate anxiety. After the intervention, 50% of patients experienced mild anxiety. The Wilcoxon test showed a P-value of 0.000, indicating a significant effect of Islamic-based autogenic relaxation intervention on anxiety levels in CVA patients. Conclusion : Islamic-based autogenic relaxation therapy can reduce anxiety by calming the mind, reducing stress, and motivating patients to be more active.